Importance of identification and treatment of Raynaud''s phenomenon. Issue 5 (October 2007) - Frech, Tracy; Sawitzke, Allen
Raynaud''s phenomenon (RP) is a stress- or cold-temperature-induced, recurrent, but transient digital ischemia, which is characterized by a demarcated pallor and followed by a re-flow of blood to the digits, that appears as erythema, cyanosis or both. RP is differentiated into primary and secondary forms. Identification of the form secondary to autoimmune phenomenon is essential, because of the potential for complicated outcomes, internal organ involvement and more frequent need for pharmacological treatment. When a secondary form of RP is identified, especially in the case of systemic sclerosis (SSc), internal organ involvement from the disease process directs therapy. It is thought that this internal organ involvement is a manifestation of the same vasospastic propensity that RP represents. Thus, it is possible that a heightened understanding of the pathogenesis of RP demands a more aggressive intervention for secondary RP associated with SSc. This becomes especially important as therapy, in addition to the traditional therapies that improve vasodilatation and inhibit vasoconstriction, are developed. This is possibly best illustrated through the role of statins. These agents impair abnormal vascular remodeling, possibly through effects on apoptosis of the pericyte; a cell that has the potential to develop into a vascular smooth muscle cell and fibroblast and could be important for the development of SSc.